Photoacoustic Imaging for Noninvasive Periodontal Probing Depth Measurements. (January 2018) - Lin, C.Y.; Chen, F.; Hariri, A.; Chen, C.J.; Wilder-Smith, P.; Takesh, T.; Jokerst, J.V.
The periodontal probe is the gold standard tool for periodontal examinations, including probing depth measurements, but is limited by systematic and random errors. Here, we used photoacoustic ultrasound for high–spatial resolution imaging of probing depths. Specific contrast from dental pockets was achieved with food-grade cuttlefish ink as a contrast medium. Here, 39 porcine teeth (12 teeth with artificially deeper pockets) were treated with the contrast agent, and the probing depths were measured with novel photoacoustic imaging and a Williams periodontal probe. There were statistically significant differences between the 2 measurement approaches for distal, lingual, and buccal sites but not mesial. Bland-Altman analysis revealed that all bias values were < ±0.25 mm, and the coefficients of variation for 5 replicates were <11%. The photoacoustic imaging approach also offered 0.01-mm precision and could cover the entire pocket, as opposed to the probe-based approach, which is limited to only a few sites. This report is the first to use photoacoustic imaging for probing depth measurements with potential implications to the dental field, including tools for automated dental examinations or noninvasive examinations.